Age‐related differences in social influence on risk perception depend on the direction of influence. (26th July 2017) - Knoll, Lisa J.; Leung, Jovita T.; Foulkes, Lucy; Blakemore, Sarah‐Jayne
ABSTRACT: Adolescents are particularly susceptible to social influence. Here, we investigated the effect of social influence on risk perception in 590 participants aged eight to fifty‐nine‐years tested in the United Kingdom. Participants rated the riskiness of everyday situations, were then informed about the rating of these situations from a (fictitious) social‐influence group consisting of teenagers or adults, and then re‐evaluated the situation. Our first aim was to attempt to replicate our previous finding that young adolescents are influenced more by teenagers than by adults . Second, we investigated the social‐influence effect when the social‐influence group's rating was more, or less, risky than the participants' own risk rating. Younger participants were more strongly influenced by teenagers than by adults, but only when teenagers rated a situation as more risky than did participants. This suggests that stereotypical characteristics of the social‐influence group – risk‐prone teenagers ‐ interact with social influence on risk perception.